Absorption Troughs of Lyα Emitters in HETDEX - Laurel H. Weiss; Dustin Davis; Karl Gebhardt; Simon Gazagnes; Mahan Mirza Khanlari; Erin Mentuch Cooper; John Chisholm; Danielle Berg; William P. Bowman; Chris Byrohl; Robin Ciardullo; Maximilian Fabricius; et al. (The Astrophysical Journal, 2024)
The Hobby–Eberly Telescope Dark Energy Experiment (HETDEX) is designed to detect and measure the redshifts of more than 1 million Ly α emitting galaxies (LAEs) 1.88 < z < 3.52. In addition to its cosmological measurements, these data enable studies of Ly α spectral profiles and the underlying radiative transfer. Using the roughly half a million LAEs in the HETDEX Data Release 3, we stack various subsets to obtain the typical Ly α profile for the z ∼ 2–3 epoch and to understand their physical properties. We find clear absorption wings around Ly α emission, which extend ∼2000 km s ^−1 both redward and blueward of the central line. Using far-UV spectra of nearby (0.002 < z < 0.182) LAEs in the COS Legacy Archive Spectroscopic Survey treasury and optical/near-IR spectra of 2.8 < z < 6.7 LAEs in the Multi Unit Spectroscopic-Wide survey, we observe absorption profiles in both redshift regimes. Dividing the sample by volume density shows that the troughs increase in higher-density regions. This trend suggests that the depth of the absorption is dependent on the local density of objects near the LAE, a geometry that is similar to damped Ly α systems. Simple simulations of Ly α radiative transfer can produce similar troughs due to absorption of light from background sources by H i gas surrounding the LAEs.